Answer:
1) Combine like terms
2) ![\sqrt[3]{x} =3](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%7D%20%3D3)
3) cube both sides of the equation
4) ![4\sqrt[3]{27} +8\sqrt[3]{27}=36](https://tex.z-dn.net/?f=4%5Csqrt%5B3%5D%7B27%7D%20%2B8%5Csqrt%5B3%5D%7B27%7D%3D36)
5) 4(3) + 8(3) = 36
Step-by-step explanation:
1) Combine like terms
2) ![\sqrt[3]{x} =3](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%7D%20%3D3)
3) cube both sides of the equation
4) ![4\sqrt[3]{27} +8\sqrt[3]{27}=36](https://tex.z-dn.net/?f=4%5Csqrt%5B3%5D%7B27%7D%20%2B8%5Csqrt%5B3%5D%7B27%7D%3D36)
5) 4(3) + 8(3) = 36
Answer:
1: 7/10
2: 3/10
3: 4/8 (2/4 or 1/2 if you need to simplify it)
Step-by-step explanation:
1: Convert 2/5 to tenths by multiplying the denominator and numerator by two. 3/10 plus 4/10 is 7/10
2: Convert 4/5 and 1/2 to tenths.
4/5 is going to be 8/10, 1/2 is going to be 5/10.
Subtract 5/10 from 8/10 to get 3/10
3: Convert 1/4 to eighths to get 2/8. Then add 2/8 and 2/8 to get 4/8.
Answer:
-1
Step-by-step explanation:
We can plug in -3 for x and solve:
f(-3) = -3 + 2
= -1
Answer: There are 350 consumers who purchase frozen yogurt.
Step-by-step explanation:
Since we have given that
Number of consumers polled =360
Number of consumers who purchased ice- cream = 260
Number of consumers who purchased both ice- cream and frozen yogurt = 250
We need to find the number of consumers who purchased frozen yogurt,
Let A denotes who purchased ice-cream
and B denotes who purchased frozen yogurt.
As we know the formula
![n(A\cup B)=n(A)+n(B)-n(A\cap B)\\\\360=260+n(B)-250\\\\360=10+n(B)\\\\360-10=n(B)\\\\350=n(B)](https://tex.z-dn.net/?f=n%28A%5Ccup%20B%29%3Dn%28A%29%2Bn%28B%29-n%28A%5Ccap%20B%29%5C%5C%5C%5C360%3D260%2Bn%28B%29-250%5C%5C%5C%5C360%3D10%2Bn%28B%29%5C%5C%5C%5C360-10%3Dn%28B%29%5C%5C%5C%5C350%3Dn%28B%29)
Hence, there are 350 consumers who purchase frozen yogurt.
Answer:
∠ ABE = 46°
Step-by-step explanation:
Since BE bisects ∠ ABC , then
∠ EBC = ∠ ABE, substitute values
4x - 6 = 2x + 20 ( subtract 2x from both sides )
2x - 6 = 20 ( add 6 to both sides )
2x = 26 ( divide both sides by 2 )
x = 13
Thus
∠ ABE = 2x + 20 = 2(13) + 20 = 26 + 20 = 46°